DIVERSITY OF RACES AND ITS CONTRIBUTION TO ENGLISH PHONOLOGICAL ERROR - Kayyis, Rahmatika (STKIP Muhammadiyah Pringsewu, 2018)
This research analyses English Phonological Errors produced by the diversity races in Lampung, those are: Â Jasengnese, Javanese, Lampungnese, Palembanganese, Semendonese, and Sundanese. Â It aims to find out which aspects of Phonological errors that are pronounced. The design of the research was a case study in the form of qualitative research using the principle of contrastive analysis to analyze the data. The participants were chosen regarding as representative among those races who learn English for the foreign language in semester three and five of English Education Department in STKIP Muhammadiyah Pringsewu Lampung. Â Recording pronunciation test and interview were used to collect the data. Phonetics transcription online were used to find the error and transcribe it into phonetics symbol. As the findings, this research focuses on 50% errors. Jasengnese committed errors on /d/, /ÉË/, /uË/, /ÊÉ/, stressing word at the first, middle, last, the intonation was in rising and falling intonation, and / iË/, /ÉÊ/, /aÉª/, /ÉË/ in complementary distribution. Javanese commited errors on /d/, /b/, /p/, /g/, stressing words at the middle, last. Lampungnese committed errors on /f/, /v/, /p/, /É/, stressing words at the first, middle, last, rising and falling intonation, and / iË/, /ÉÊ/, /aÉª/, /ÉË/ in complementary distribution. Palembangnese committed errors on /b/ and /d/, /ÉÉª/, /eÉ/, /ÉªÉ/, /ÊÉ/, stressing word at the first, middle, last, the intonation was in rising and falling intonation, and /Ê/, /ÉÊ/, /i:/ /aÉª/, / /ÉË/, and /iËst/ in complementary distribution. Semendonese committed errors on /É/, /Ê /, /iË/, /uË/, /ÉË/,Â stressing word at the first, middle, last, the intonation was in rising and falling intonation, and /iËÊ§/, /Ê/, /ÉÊ/, /i/, /Éª/, /ÉËst/Â in complementary distribution. Sundanese Semendonese committed errors on /É/, /Ê /, /iË/, /uË/, /ÉË/, /p/, /v/, stressing word at the first, middle, last, the intonation was in rising and falling intonation, and /iËÊ§/, /Ê/, /ÉÊ/, /i/, /Éª/, /ÉËst/Â in complementary distribution. In conclusion, Jasengnese, Javanese, Lampungnese, Palembanganese, Semendonese, and Sundanese had problem in long vowel, voiced consonant, stressing word at the first, middle, and last, and falling and rising intonation. They were influenced by age, accent, and mother language in English Phonetics and Phonology was strong enough. Some method and technique can be applied to reduce studentsâ problem in pronouncing English words.Â